NILAI EKONOMI SPASIAL DALAM PEMANFAATAN TAMAN WISATA PERAIRAN GILI MATRA UNTUK WISATA SELAM DI KABUPATEN LOMBOK UTARA, NUSA TENGGARA BARAT - Fredinan Yulianda; Lalu Solihin Solihin; Tridoyo Kusumastanto; Akhmad Fauzi (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Sustainability is not only measured by the ecological aspect, but also the economic and social aspects. In the Taman Wisata Perairan (Tourism Waters Park) of Gili Indah Village, there are 26 dive sites. In this study only used 12 point dive as study locations. Each locations have different economic value and different appeal. The purpose of this study was to analyze the economic capacity of sustainable water tourism area based on carrying capacity. Data analysis using combination of analysis between the carrying capacity of area and analysis of the economic value of the water area. The results showed that the total area of 9.404 ha of areas devoted to diving tourism, it can accommodate the number of tourist as much as 112.850 people per year, or as many as 3.762 people per day. While the existing condition indicates that the total number of visitors who made a dive as much as 15.467 people with the frequency of dives as much as 35.717 dives per year spread across the 12 point dive sites. Each rating average dives twice a day. Economic capacity based on frequency of dives amounted to 132.3 billion rupiah per year.Keywords: Water Tourism, Carrying Capacity, Economic Capacity, Sustainability